Space and time in Amos 7: Reconsidering the third vision - Heyns, Dalene (Old Testament essays, 1997)
The third vision of Amos is problematic. This is owing to the meaning of ... and the relation of the vision to the prophetic narrative which has been inserted between the third and fouthh visions. It is here argued that the translation of ... =plumbline fits the context of the seasonal sequence, when a plumbline is understood as an instrument for time measurements and calendrical calculations. Situated in the centre of the vision series, the third vision marks the point where Yahweh's mercy tums to judgement. If the vision portrays Yahweh's measuring of space and time, signifying his cosmic control over the forces of history and nature, its function in the series can be better explained.